A Study on Pharmacokinetic Functionalities and Safety Margins of an Optimized Simvastatin Nanoformulation - Aftab Ahmad; Unnikrishnan Meenakshi Dhanalekshmi; Kailasam Koumaravelu; Arul Prakash Francis; Shah Alam Khan; Mohammed F. Abuzinadah; Nandakumar Selvasudha (MDPI AG, 2023)
A pharmaceutical formulation with favorable pharmacokinetic parameters is more likely to be efficacious and safe to overcome the failures of the drug resulting from lack of efficacy, poor bioavailability, and toxicity. In this view, we aimed to evaluate the pharmacokinetic functionalities and safety margin of an optimized CS-SS nanoformulation (F40) by in vitro/in vivo methods. The everted sac technique was used to evaluate the improved absorption of a simvastatin formulation. In vitro protein binding in bovine serum and mice plasma was performed. The formulation's liver and intestinal CYP3A4 activity and metabolic pathways were investigated by the qRT-PCR technique. The excretion of cholesterol and bile acids was measured to demonstrate the formulation's cholesterol depletion effect. Safety margins were determined by histopathology as well as fiber typing studies. In vitro protein binding results revealed the existence of a high percentage of free drugs (22.31 ± 3.1%, 18.20 ± 1.9%, and 16.9 ± 2.2%, respectively) compared to the standard formulation. The controlled metabolism in the liver was demonstrated from CYP3A4 activity. The formulation showed enhanced PK parameters in rabbits such as a lower Cmax, clearance, and a higher Tmax, AUC, Vd, and t1/2. qRT-PCR screening further proved the different metabolic pathways followed by simvastatin (SREBP-2) and chitosan (PPAR-γ pathway) in the formulation. The results from qRT-PCR and histopathology confirmed the toxicity level. Hence, this pharmacokinetic profile of the nanoformulation proved it has a unique synergistic hypolipidemic modality.